2020
DOI: 10.1002/lary.29207
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of 67 Studies with Presenting Symptoms and Laboratory Tests of COVID‐19 Patients

Abstract: Objectives/Hypothesis: The objective of this meta-analysis was to look at the pooled prevalence of symptoms, laboratory tests, and imaging of all COVID-19 infected patients. This will allow better identification of potential COVID-19 patients and take appropriate precautions.Study design: Meta analysis. Methods: We searched three databases, PubMed, EMBASE, and Ovid to identify studies published between Dec-2019 and May-2020. All studies reporting upper-aerodigestive symptoms of COVID-19 infection were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 81 publications
0
38
1
Order By: Relevance
“…Fever has been widely reported as one of the most frequent symptoms in patients with coronavirus disease 2019 . In a recent meta-analysis of 67 studies and 8302 COVID-19 patients, above normal body temperature was observed in over twothirds of positive cases (69%; 95% confidence interval [95%CI], 62-76%) [1]. Similar rates of fever were reported in a parallel meta-analysis based on 76 studies and totalling 11,028 COVID-19 patients across multiple countries (72%; 95%CI, 67-78%) [2], as well as in another meta-analysis of 71 articles involving 11,671 children with COVID-19 (56%; 95%CI, 50-51%) [3].…”
Section: Sirmentioning
confidence: 99%
“…Fever has been widely reported as one of the most frequent symptoms in patients with coronavirus disease 2019 . In a recent meta-analysis of 67 studies and 8302 COVID-19 patients, above normal body temperature was observed in over twothirds of positive cases (69%; 95% confidence interval [95%CI], 62-76%) [1]. Similar rates of fever were reported in a parallel meta-analysis based on 76 studies and totalling 11,028 COVID-19 patients across multiple countries (72%; 95%CI, 67-78%) [2], as well as in another meta-analysis of 71 articles involving 11,671 children with COVID-19 (56%; 95%CI, 50-51%) [3].…”
Section: Sirmentioning
confidence: 99%
“…The symptoms were mostly related to respiratory symptoms including fever, cough, difficulty in breathing, loss of sense of smell or taste, gasping, fatigue and diarrhoea. In more severe cases, symptoms such as acute respiratory failure, pneumonia, persistent chest pain or pressure have been observed [6,16,17]. A meta-analysis study on the prevalence of COVID-19 symptoms in adults demonstrated the prevalence of symptoms in the systemic, respiratory, ear, nose, throat, gastrointestinal, eyes and central nervous system [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fever/chills, cough, shortness of breath/difficulty breathing, fatigue, muscle/body aches, headache, sore throat, nasal congestion, rhinorrhea, nausea/vomiting, diarrhea and loss of taste/ smell are features of COVID-19 [1]. Pediatric patients generally show milder symptoms than adults, and typical symptoms include cough, sore throat, fever, and/or diarrhea [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Fever/chills, cough, shortness of breath/difficulty breathing, fatigue, muscle/body aches, headache, sore throat, nasal congestion, rhinorrhea, nausea/vomiting, diarrhea and loss of taste/ smell are features of COVID-19 [1]. Pediatric patients generally show milder symptoms than adults, and typical symptoms include cough, sore throat, fever, and/or diarrhea [1,2]. Current best estimates show up to 40% of infectious individuals including both adults and children may be clinically asymptomatic, though it is known children are asymptomatic at higher rates [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation